2006
DOI: 10.1001/archotol.132.2.179
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Mometasone Furoate Nasal Spray for the Treatment of Nasal Polyposis

Abstract: Objective: To evaluate the efficacy and safety of mometasone furoate nasal spray (NS) for the treatment of nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 27 publications
7
134
1
7
Order By: Relevance
“…105 In that trial, mometasone furoate 200 µg once or twice daily produced greater reductions in polyp grade at endpoint compared with placebo, with differences reaching statistical significance for twice daily dosing (p=0.04). Both regimens achieved statistically superior improvements from baseline in congestion and/or obstruction score vs placebo by the end of the first month.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 91%
See 1 more Smart Citation
“…105 In that trial, mometasone furoate 200 µg once or twice daily produced greater reductions in polyp grade at endpoint compared with placebo, with differences reaching statistical significance for twice daily dosing (p=0.04). Both regimens achieved statistically superior improvements from baseline in congestion and/or obstruction score vs placebo by the end of the first month.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 91%
“…[102][103][104][105][106][107] In 183 patients with moderate-sized nasal polyps causing clinically significant symptoms, budesonide aqueous nasal spray at a dose of 128 µg once or twice daily, or 256 µg once daily for eight weeks significantly reduced polyp size (p<0.01) and improved peak nasal inspiratory flow (p<0.001) compared with placebo. 106 Combined and individual symptom scores (blocked nose, runny nose, and sneezing) and sense of smell also improved significantly in all budesonide-treated groups.…”
Section: Acute Rhinosinusitis and Nasal Polyposis: Association With Amentioning
confidence: 99%
“…Several randomized clinical trials have shown these medications to be effective treatments for NP (table 1) [8,13,64,65,66,67,68,69,70,71,72,73,74,75,76]. There are few or no randomized, controlled published trials that evaluate the effectiveness of the INSs flunisolide, triamcinolone, or beclomethasone in polyposis [77].…”
Section: Resultsmentioning
confidence: 99%
“…1b) for 5 days, then twice daily until the bottle runs out Maintenance therapy with fluticasone (drops, spray) or mometasone (spray) is recommended as these have lower bioavailability, unlike betamethasone nasal drops [83][84][85][86].…”
Section: Text Box 4: Medical Polypectomymentioning
confidence: 99%